STRATEGI PENGUASAAN KELAS DALAM MICRO TEACHING UNTUK MENINGKATKAN KETERAMPILAN MENGAJAR MAHASISWA - Harahap, Hasnaun Nasika; Ginting, Rahmadani Fitri (Sindoro: Cendikia Pendidikan, 2024)
Micro teaching is an approach that allows students to practice teaching techniques in a structured and guided manner on a small scale. Micro teaching provides students with the opportunity to practice various aspects of teaching, including lesson planning, delivery of material, and classroom management. This research uses a descriptive qualitative approach to explore classroom mastery strategies in micro teaching to improve students' teaching skills. The subjects of this research were education program students who were or had taken micro teaching courses at an educational university. To ensure the validity of the data, this research uses data source triangulation techniques, namely comparing data from interviews, observations and documentation to ensure the consistency and validity of the findings. The results of this research show that Micro teaching provides opportunities for students to practice using these various strategies in controlled situations and receive constructive feedback, so that they can improve and develop their teaching skills on an ongoing basis. Good classroom mastery not only helps students in managing student behavior, but also contributes to increasing overall learning effectiveness. Thus, appropriate classroom mastery strategies during micro teaching are very important in shaping students into professional teacher candidates who are ready to face real challenges in the world of education.